Increase of the Availability of Machinery in a Food Company Applying the TPM, SMED and RCM Methodologies - Castañeda, Sair (2024)
The food industry stands as a pivotal contributor to economic and efficient production in contemporary societies. In recent years, Peru has witnessed a notable upswing in the industrial food sector, characterized by the automation of production processes and the consequential shift from manual labor to machinery. Despite these advancements, a pervasive challenge persists – the suboptimal availability of critical machinery due to various failures, leading to operational disruptions and additional costs. This challenge is empirically examined through a case study measuring machinery availability via MTBF and MTTR indicators, revealing suboptimal values according to "World Class" benchmarks, as reflected in the efficiency value measured by the OEE indicator. In response to these findings, a practical and economically viable model adapted to the unique needs of the food sector is proposed. Leveraging fundamental indicators such as MTBF, MTTR, and OEE, deviations from "World Class" standards are identified. The proposed model strategically integrates the second pillar of Total Productive Maintenance (TPM), the Single-Minute Exchange of Die (SMED) methodology, and the third TPM pillar into the Reliability-Centered Maintenance (RCM) tool. This study underscores the inefficiencies stemming from suboptimal machinery availability, highlighted by non-ideal MTBF, MTTR, and OEE values. The proposed model, focusing on TPM and SMED methodologies, demonstrates a tangible enhancement in machinery availability, translating into heightened productivity and reduced operational costs. The proposed improvements, once implemented, are anticipated to deliver enduring benefits, aiming for a sustained positive impact on productivity and cost-efficiency within the food industry.